INTERNALISASI NILAI AKUNTABILITAS DALAM TUGAS PROYEK UNTUK MENGEMBANGKAN KECERDASAN SPIRITUAL MAHASISWA - Ketut Nurhayanti; I Gusti Ayu Astri Pramitari (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
the purpose of this study is to make student learning assessment instruments for Hindu subjects in the form of project assignments that contain the basic values of accountability as an effort to develop students' spiritual intelligence. This study uses a type of qualitative research assisted with qualitative data. Data of research subjects were 28 respondents using observation, interview and questionnaire data collection techniques. The data analysis technique uses descriptive qualitative, which is to describe the symptoms or results of the research in a narrative manner. The results of this study indicate that the application of project tasks that contain the value of accountability is able to develop an attitude of responsibility, independence and respect for others to students. This attitude is part of behavior that reflects spiritual intelligence.